2018
DOI: 10.1051/e3sconf/20183108015
|View full text |Cite
|
Sign up to set email alerts
|

The Application Of Liquid Fertilizer Made Of Traditional Market Organic Wastes On Growth Of Setaria Grass (Setaria splendida Stapf)

Abstract: There are hugh amount of traditional market organic wastes that may polute the environment. In general, the wastes are utilized for compost making and liquid fertilizer as well for plant. The use of liquid fertilizer from organic wastes of traditional markets opens up opportunities for misplaced cultivation of Setaria grass (Setaria splendida Stapf), which is required by ruminant farms. This research was conducted to evaluate the best mixture of water to the fertilizer in term of its effectiveness on the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…The measurement results showed that the average size of the Setaria Splendida Stapf plant height was 42.76 cm, in the range of 31.33 cm -52.15 cm. These results are lower than the results of [10] which showed that the size of the Setaria Splendida Stapf plant height was 50.17 cm, but at almost the same range. Table 3 shows that the older the plants, the higher their height [11], the highest increase in size between the age of 40 days to 45 days which is as much as 5.22 cm while between 35 -40 days, the addition is only 1.96 cm.…”
Section: Effect Of Defoliation Age and Dosage Of Liquid Of Organic Fecontrasting
confidence: 76%
See 1 more Smart Citation
“…The measurement results showed that the average size of the Setaria Splendida Stapf plant height was 42.76 cm, in the range of 31.33 cm -52.15 cm. These results are lower than the results of [10] which showed that the size of the Setaria Splendida Stapf plant height was 50.17 cm, but at almost the same range. Table 3 shows that the older the plants, the higher their height [11], the highest increase in size between the age of 40 days to 45 days which is as much as 5.22 cm while between 35 -40 days, the addition is only 1.96 cm.…”
Section: Effect Of Defoliation Age and Dosage Of Liquid Of Organic Fecontrasting
confidence: 76%
“…As a potential natural resource in human life, it is possible to need another strategy in the utilization of liquid of organic fertilizer from market conventional system waste in its application for feed crops [10]. These strategies include fertilization time, fertilizer dosage, fertilization technique, mixture with other materials and so on.…”
Section: Effect Of Defoliation Age and Dosage Of Liquid Of Organic Fementioning
confidence: 99%